Seasonal Phytoplanktonic Diversity Of Kalisil River In Keladevi Wildlife Sanctuary, District Karauli, Rajasthan, India - SHYAM S. SHARMA,; GAJENDRA P. SINGH,; VIJENDRA K. SHARMA, (International Journal of Pharma and Bio Sciences, 2012)
Bio-monitoring is necessary to study the ecological quality of various ecosystems since biological communities incorporate the environmental effects of water quality. The water samples were collected for two years and the data on seasonal studies regarding water chemistry and phytoplanktonic variation of Kalisil River situated in and around the Keladevi wildlife sanctuary, district Karauli, Rajasthan (India) were recorded. Although, the results show fluctuations in the various physicochemical properties of water in different seasons, the values of all parameters are higher in summer except the dissolved oxygen. A total of 36 algal genera with 60 species belonging to four classes have been accounted from three sites of the river. A limited number of these were recorded throughout the year, while others were distributed in different seasons mainly in summer and winter seasons. During the summer season, Chlorophyceae (17 species) and Cyanophyceae (15 species) were the most dominant group. On the other hand, Bacillariophyceae (12 species) was most dominant during winter. The pollution of river is evident with the presence of algae like, Chlorogonium euchlorm, Chlorella vulgaris, Gonium compactum, Scendesmus opoliensis, Merismopdia sp., Oscillatoria trichoides, Euglena acus and Navicula minusa throughout the investigation.